Synthetic Approaches towards Photoactive Metal-Organic Frameworks - Souza Martins, Luana (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2021)
Metal-organic frameworks (MOFs) are a class of hybrid inorganic-organic materials. They are composed of metal-containing units linked by organic linkers through strong bonds, forming high dimensional frameworks. MOFs are exciting materials for their designability and exceptional porosity, leading to a wide range of potential industrial applications. In particular, applications related to light driven transformations and energy technologies as photocatalytic conversions and fuel cells have made them objects of extensive academic study. The tunability of MOFs towards these potential applications is guided by an approach known as reticular synthesis. The approach emphasises the judicious assembling of rigid molecular building blocks into predetermined networks. The research outlined in this thesis focuses on the synthesis and characterisation of novel coordination polymers and MOFs with functionalities that can be exploited in light driven chemical transformations and related applications. The first chapter introduces the reader to the subject area of MOFs. It comprises the foundation for the design and synthesis of representative frameworks reported in the literature as well as an overview of potential applications. Chapter two details the synthesis of a multidentate ligand 4'-(1Himidazo[4,5- f][1,10]phenanthrolin-2-yl)-[1,1'-biphenyl]-4-carboxylic acid (HNCP2) containing N-donors and O-donors from the phenanthroline and a carboxylic acid moieties respectively. The synthesis and structural characterisation of a series of coordination polymers based on various MII metal ions are also described. The work presented on this chapter aimed to understand the impact of synthetic conditions (specifically the use of modulators) on the crystallisation process of coordination polymers derived from phenanthroline based ligands and MII metal ions. In chapter three, a photoactive, hetero-metallic CoII/RuII-based MOF with a channel aperture of ca. 21 Å, is reported as Photo-MOF. The MOF was crystallised from CoII salt and a phenanthroline-based tritopic metallo-ligand [Ru(HNCP)3](PF6)2 (named H3LRu) in the presence of a modulator. The photophysical properties of the MOF are derived from the RuII nodes giving rise to emission centred at ca. 620 nm and relatively long triplet 3MLCT lifetimes. In addition to the optical attributes, the 1H-imidazo [4,5-f][1,10]-phenanthroline ligand imparts structural functionality to the MOF which is composed of alternating CoII- and RuII-based nodes. The framework maintains its integrity upon removal of constitutional solvent and shows gas sorption behaviour that is characteristic of mesoporous materials promoting high CO2 sorption capacities and selectivity over N2. Electrochemical synthesis of the obtained material was used as an alternative synthetic pathway. The deposition method allowed us to functionalise a conductive substrate through an energy-efficient process in reduced reaction time. The characterisation of the obtained thin film confirms the identity of the film as microporous layers of Photo-MOF, which is corroborated by structural characterisation as well as photophysical and imaging studies. Chapter four contains the optimised synthetic pathway of a novel organic ligand 5-((4- ([2,2':6',2''-terpyridin]-4'-yl)phenyl)ethynyl)isophthalic acid (H2TpyPEI) and a ditopic RuII metallo-ligand H2LRu crystallographically identified as [Ru(H2TpyPEI)Tpy](PF6)2. The metallo-ligand comprises a [Ru(tpy)2]2+ moiety that has been reported as an efficient photosensitiser used in light-driven, hydrogen evolution reaction. Photophysical studies performed on metallo-ligand reveal relatively intense absorption in the visible region. H2LRu was employed in the synthesis of a 2D heterometallic MnII/RuII-MOF, which is comprised of {[Ru(tpy)2]} as light-harvesting unit and a {Mn2(COO)4]} dinuclear cluster with unsaturated metal sites that combined can act as photocatalytic active platform. Chapter five conveys a preliminary study on the impact of the use of structurally related organic ligands on the frameworks topology. Two carboxylate-based ligands: isophthalic acid (H2IP) and an asymmetrically elongated, trifunctional polycarboxilate derivative (H3CPEIP) were used in the synthesis of two CoII-MOFs 5.1 and 5.2 respectively. The structures crystallise at corresponding synthetic conditions and contain an identical dinuclear CoII cluster. 5.2 incorporates an additional mononuclear cluster that forms in presence of the third carboxylate functionality. As expected both structures exhibit 2D layered architectures with unblocked channels. 5.1 exhibits smaller triangular and larger hexagonal channels and a topology typically classified as a Kagomé lattice while 5.2 presents an novel topology which is characterised by the vertex symbol (4.62)·(42.62.82). Chapter six provides concluding remarks and offers and outline of possible future studies related to applications of the presented materials in photocatalysis. Finally, chapter seven provides detailed experimental procedures and characterisation of all the compounds and intermediates described throughout the thesis.
ACCEPTED
Keywords: Smart & Sustainable Planet